(untitled) (Revista Lusófona de Educação, 2021)
Recensão crítica da obra de Teodoro, A. (2020). Contesting the Global Development of Sustainable and Inclusive Education. Education Reform and the Challenges of Neoliberal Globalization. New York and London: Routledge.